2021
DOI: 10.1016/j.ijcard.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and reference values for cardiopulmonary exercise testing in the adult Chinese population – The Xiangya hospital exercise testing project (the X-ET project)

Abstract: Background: Reference values of cardiopulmonary exercise testing (CPX) vary with race/ethnicity. Chinese Americans are the fastest-growing racial/ethnic group in the United States. However, there is limited information about the reference values of cardiopulmonary exercise testing (CPX) variables in the Chinese population. Methods: As part of the Xiangya Hospital Exercise Testing project (the X-ET project), this cross-sectional study screened 20,696 consecutive CPXs performed by 17,802 unique individuals at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Anthropometric features such as weight and height of the Caucasian and Asian population are different. For example, height, weight and BMI of subjects in an Asian population 14 16 19 20 21 22 23 were similar to those of the present study, but lower than those of primarily Caucasians. 12 13 18 As above, the predicted VO 2 max using Yaoshan equation using the Asian population had good agreement with our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Anthropometric features such as weight and height of the Caucasian and Asian population are different. For example, height, weight and BMI of subjects in an Asian population 14 16 19 20 21 22 23 were similar to those of the present study, but lower than those of primarily Caucasians. 12 13 18 As above, the predicted VO 2 max using Yaoshan equation using the Asian population had good agreement with our study.…”
Section: Discussionsupporting
confidence: 84%
“…Most reference values and prediction equations are available for the Caucasians only. 10 11 12 13 In contrast, there are few reference values for the Asians 14 15 16 and no reference value of VO 2 max for Koreans. There are no reliable exercise capacity equations for VO 2 max applicable to Koreans.…”
Section: Introductionmentioning
confidence: 99%
“…Mean O 2peak values reported in our study was higher compared with that reported by Dun and colleagues in 2021 among Chinese patients who had no symptoms recorded. For example, for people aged from 20 to 30 years in both genders, mean O 2peak values were about 30% higher in our study [ 14 ]. We believe this discrepancy should be mainly due to the difference in source of the study samples.…”
Section: Discussionmentioning
confidence: 67%
“…However, the safety concerns for exercise are a real hurdle to the mass physical exercise endeavor. To help Chinese people exercise safely, reference values of CRF based on healthy Chinese individuals from the general population are also urgently needed, though a recent study of O 2peak reference values was reported using the hospital electronic medical record data of Chinese individuals without specific clinical complaints [ 14 ]. The importance of research on normal references of CRF based on healthy individuals from general population has been emphasized by the American Heart Association (AHA) in 2013 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…From August to November 2021, all participants performed a cardiopulmonary exercise test (CPET) 1 week before practicing X-CircuiT in Xiangya Hospital, Central South University, to obtain the peak heart rate (HR peak ), peak oxygen uptake (VO 2peak ), and the individual regression equation of HR and VO 2 . The standard of procedure for performing CPET has been described previously ( 23 , 24 ). The HR and VO 2 data collected from the CPET were used to fit the individual regression equation of HR-VO 2 , according to which we calculated the VO 2 during X-CircuiT.…”
Section: Methodsmentioning
confidence: 99%